Evaluation of Sedation Practices and Characteristics of Mechanically Ventilated Patients - Angel Josey, Precious (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Mechanical ventilation is a form of life support. Standardized sedation practices must be followed in every intensive care unit (ICU) for patients who are mechanically ventilated. Length of mechanical ventilation increases due to excessively sedating the patients without following proper sedation protocols. Aim: This study aims to assess the current sedation practices in ICUs, to explore characteristics of patients on mechanical ventilator, and to correlate total amount of sedation used and length of mechanical ventilation. Methodology: Quantitative approach, descriptive survey was adopted. One hundred mechanically ventilated-sedated patients in ICUs using non-probability convenient sampling method were selected. Patients were evaluated using observational checklists and standardized RASS scale. Results: Result shows that maximum 25 (25%) patients were between the age group of 41 and 50 years and 62 (62%) of patients were male. Maximum 44 (44%) of patients got admitted due to respiratory conditions. Among 100 (100%) of patients, 51 (51%) of patients were heavily sedated and were unarousable on day 1. Maximum 15 (15%) of patients received highest amount of sedation for 4 days and 58 (58%) of patients went to shock on the 1st day. When 100 (100%) of patients are being considered, 86 (86%) of patients survived and 14 (14%) of patients died due to various reasons. Conclusion: A positive correlation coefficient can be seen between total amount of sedation and length of mechanical ventilation also with significant association between length of mechanical ventilation and outcome of patients.